Observations of Wave Height Amplification Behind an Oyster Castle Breakwater System in a High-Energy Environment: Gandys Beach, NJ - Bredes, Amy L.; Miller, Jon K.; Kerr, Laura; Brown, Dana Rose (Frontiers in Built Environment, 2022)
This study reports findings of an analysis of modifications to the incident wave field caused by constructed Oyster Castle® breakwater systems at Gandys Beach Preserve in Downe Township, NJ. The Nature Conservancy’s (TNC) Gandys Beach Preserve is a one-mile stretch of beach located along with intertidal mud flats, sandy beaches, tidal creeks, and salt marshes. Gandys Beach can be classified as a high-energy environment, with open water fetches exceeding 30 miles, and a tidal range on the order of 2 meters. The Gandys Beach living shoreline project was designed and constructed by TNC in partnership with the U.S. Fish and Wildlife Service (USFWS) to investigate the effectiveness of various natural and nature-based features (NNBFs) in protecting and enhancing salt marshes and beaches in high(er) energy environments. Many of the NNBF techniques used at Gandys Beach, such as Oyster Castle® block breakwaters (Oyster Castles), had only been implemented at smaller scales in New Jersey prior to the project. Stevens was contracted by USFWS/TNC to evaluate the impact of the breakwater systems on incident waves. Four breakwater sections along the beach were selected to monitor wave attenuation. Month-long deployments of wave staffs and pressure sensors occurred in the summer and winter of 2019. Analysis of the data indicates that when crests of the Oyster Castles are exposed the breakwater system effectively attenuates waves. However, when the structures are submerged, wave height attenuation decreases, and under certain conditions wave heights behind Oyster Castles can be amplified more than 80%. These results are troubling, especially in areas experiencing sea level rise where the frequency of submergence will likely increase in the future. Due to the complex nature of Gandys Beach, exact mechanisms causing this amplification remain uncertain. Furthermore, transmission coefficients (Kt) above 1 are not typically modeled in existing empirical equations. Seabrook and Hall 1998 is the only studied empirical formula that indicated an amplification of the Hs as observed during these field deployments and therefore was used to model Kt. However, poor agreement between the modeled and observed Kt was found and a better predictive tool is needed.